Laboratory modeling of dust impact detection by the Cassini spacecraft. (July 2018) - Nouzák, L.; Hsu, S.; Malaspina, D.; Thayer, F.M.; Ye, S.-Y.; Pavlů, J.; Němeček, Z.; Šafránková, J.; Sternovsky, Z.
Abstract: The paper presents laboratory investigations of the response of a scaled down model of the Cassini spacecraft to impacts of submicron iron grains accelerated to velocities 5–25 km/s. The aim of the study is to help in a detailed analysis and interpretation of signals provided by the RPWS (Radio Wave Plasma Science) instrument that were attributed to dust impacts onto RPWS antennas or spacecraft body. The paper describes the experimental set-up, discusses its limitations, and presents the first results. Both monopole and dipole antenna configurations are investigated. We demonstrate that the amplitude and polarity of the impulse signals recorded by antenna amplifiers depend on the voltages applied onto the antennas or the spacecraft body and briefly introduce the mechanism leading to the signal generation. The experimental results support the recent suggestion by Ye et al. (2016) that antennas operated in a dipole mode are greatly insensitive to dust impacts on the spacecraft body. The pre-peak phenomenon, commonly observed in space, is also reproduced in the measurements and explained as the induced charge on the antenna from the impact plasma cloud that is becoming non-neutral due to the escape of the faster electrons.